Análises comportamentais em larvas de zebrafish (Danio rerio) expostas a espécies de manganês de interesse ambiental - Babinski, Elaine Cristina [UNIFESP] (2017)
Manganese is an essential element. However, acute and chronic exposures for this element can result in neurotoxicity and neurodegeneration, by unclear mechanisms. Precisely, this work aimed at studying the importance of chemical speciation of manganese (Mn) on neurobehavioral and neurodegenerative changes during embryological development. In this way, zebrafish (Danio rerio) embryos were exposed during the developmental period (48-120 hours after fertilization, hpf) to chemical species of manganese (Mn (II) and Mn (III)), in neutral (white) and colored environments. The citrate of Mn(III) was the chemical species that induced the major neurobehavioral alterations on the larvae; which, often shown ansiogenic signals. The findings this work are an additional contribuition to understanding of the role chemical speciation for behavioral changes (locomotion and cognition), associated with the neurotoxicity and neurodegeneration induced by manganese.